The Use of Facebook Social Media towards the Students’ Motivation in Learning English - Sitti Halijah; Alpiyana Alpiyana (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
The purpose of this study are to know the role of Facebook social media towards the students’ motivation in learning English and also to know the factors that influence Facebook social media is used as motivation in learning English. The research design used in the research is descriptive method using qualitative that is research were producess descriptive data in the form of words or spoken people and behaviors that will be observed, including place, actor, and activity that interact synergy each other. The sampling was carried out are 30 third semester and fourth semester students of English Literature with a total population are 114 students. The findings of the study indicated that the use of Facebook social media towards the students’ motivation in learning English. The factors are interest, motivation, attention to learning, readiness to learn, teacher teaching methods, student conditions, and learning conditions.